Reduced Potential for Nitrogen Loss in Cover Crop–Soybean Relay Systems in a Cold Climate. Issue 3 (1st May 2019) - Weyers, Sharon; Thom, Matt; Forcella, Frank; Eberle, Carrie; Matthees, Heather; Gesch, Russ; Ott, Matthew; Feyereisen, Gary; Strock, Jeffery; Wyse, Don
Abstract : Winter cover crops might reduce nutrient loss to leaching in the Upper Midwest. New oilseed‐bearing cash cover crops, such as winter camelina ( Camelina sativa L.) and pennycress ( Thlaspi arvense L.), may provide needed incentives. However, the abilities of these crops to sequester labile soil nutrients are unknown. To address this unknown, N in shoot biomass, plant‐available N and P in soil, and NO3 − –N and soluble reactive P in soil water collected from lysimeters placed at 30, 60, and 100 cm were measured in cover crop and fallow treatments established in spring wheat ( Triticum aestivum L.) stubble and followed through a cover crop–soybean [ Glycine max (L.) Merr.] rotation. Five no‐till cover treatments (forage radish [ Raphanus sativus L.], winter rye [ Secale cereale L.], field pennycress, and winter camelina) were compared with two fallow treatments (chisel till and no‐till). Pennycress and winter camelina were harvested at maturity after relay sowing of soybean. Winter rye and radish sequestered more N in autumn shoot biomass, ranging from 26 to 38 kg N ha −1, but overwintering oilseeds matched or exceeded N uptake in spring, ranging 28 to 49 kg N ha −1 before soybean planting. Nitrogen uptake was reflected by reductions in soil water NO3 − –N during cover crop and intercropping phases for all cover treatments (mean = 4 mg L −1 ), compared with fallow treatments (mean = 31 mg L −1 ). Cash cover crops like pennycress and winter camelina provide both environmental and potential economic resources to growers. They are cash‐generating crops able to sequester labile soil nutrients, which protects and promotes soil health from autumn through early summer. Core Ideas: Alternative, easily established winter‐surviving covers are needed in the Upper Midwest. Cover crops sequestered N and reduced soil and soil water NO3 − –N in autumn compared with fallow. Winter oilseed crops reduced soil water NO3 − –N in autumn through soybean planting. Novel winter oilseeds provide environmental and economic incentives to enhance adoption.